Metastatic prostate cancer with negative MRI-targeted prostate biopsies: case report - Diniz, Victor S.; Lara, Celso M. C.; Damião, Ronaldo (Brazilian Journal of Health and Biomedical Sciences, 2022)
The present article reports a case of an asymptomatic patient with ascending PSA and suspected rectal examination for prostate cancer, who underwent two MRI-targeted prostate biopsies, both being negative for this neoplasm. PSMA PET/CT revealed secondary bone implant and the biopsy of the metastatic lesion showed prostate adenocarcinoma. Docetaxel-based chemotherapy associated with androgen deprivation was performed. Despite the high accuracy of MRI-targeted prostate biopsy, diagnosis can be occasionally difficult and PSMA PET/CT can help to find distant lesions and aid the diagnosis.